(untitled) (Current Problems in Rail Vehicles, 2025)
Condition monitoring of railway vehicle wheels is important not only for the safe operation of the vehicle, but also for reducing noise and vibration emissions during operation. However, wheel defects cannot be detected through static inspection alone; they can only be identified by evaluating the dynamic response during operation, which results from the interaction between the vehicle and the track. This paper presents the results of dynamic response simulations using two types of simplified models and compares them with data obtained under real operating conditions.